Reconstruction of the Paradigm of Islamic Religious Education Learning Based on the Qur'an and Hadith: An Integrative, Contextual, and Transformative Approach - Etika Pujianti; Arifah Feby Auliya; Fakhru Rozi; Ahmad Tarmizi; Riska Puspitasari; Lisa Kurniati (Global Education Journal, 2026)
This study aims to construct a conceptual framework for Islamic Religious Education learning based on the Qur'an and Hadith in an integrative and contextual manner, emphasizing the interconnectedness of students' cognitive, affective, and psychomotor dimensions in facing moral challenges in the contemporary era. This study uses a qualitative approach with a library research method to examine the foundations of the Qur'an and Hadith in Islamic Religious Education learning and their relevance to contemporary pedagogy. The primary data are verses of the Qur'an and Hadith, supported by relevant scientific literature. Data collection is carried out through documentation and systematic literature searches. Analysis uses content analysis with a thematic approach through the stages of reduction, presentation, and conclusion drawing. Data validity is maintained through source triangulation and a hermeneutic approach to produce contextual and comprehensive meaning. The results of this study indicate that Islamic Religious Education (PAI) learning based on the Qur'an and Hadith requires an integrative, contextual, and transformative paradigm reconstruction. Pedagogical principles such as wisdom, role models, dialogue, and habituation demonstrate that Islamic teachings are not merely normative but also methodological. The integration of the cognitive, affective, and psychomotor domains emphasizes the importance of holistic personality development. Furthermore, a shift from a textual to a contextual-reflective approach is necessary for more relevant and meaningful learning. Thus, Islamic Religious Education (PAI) has the potential to become an adaptive, humanistic educational model capable of shaping students' character holistically and sustainably.